Utopian images and narratives in advertising : dreams for sale - Manca, Luigi (Luigi Daniele); Manca, Alessandra; Pieper, Gail W. (Lexington Books, 2012)
Utopian Images and Narratives in Advertising: Dreams for Sale, edited by Luigi Manca, Alessandra Manca, and Gail W. Pieper, is a collection of essays which examine narratives created on the advertising page, with special focus on gender images. Through a cross-disciplinary investigation, this collection offers a varied analysis of advertising and mass media which are important for students and scholars alike.